The Problems of Teachers at SMA Negeri 2 Barru in Online-Based Bugis Language Learning - Siti Hardiyanti Jamal; Kembong Daeng (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
Problems of SMA Negeri 2 Barru Teachers in Online Learning Bugis Language. This study aims to describe the problems faced by teachers in planning, implementing, and evaluating online-based Bugis language learning. This research is a qualitative descriptive study. The informants were two Bugis language teachers. Data collection techniques include: Observation, Interview, and Documentation. The results of the study show: (1) The problem in planning online Bugis language learning is that in the RPP there is a discrepancy between the learning objectives and the KD. In the selection of learning media, teachers only choose to use chat applications as learning media. The choice of learning method the teacher only chooses the learning method for students to study individually. The preparation of teacher materials only compiles material in a reading file format, (2) Teacher problems in carrying out learning in preliminary activities, apperception activities, motivating students, and conveying learning objectives are not carried out by teachers in online learning. In the core activity, the teacher did not feel there were any obstacles in delivering the material, applying the method, and using the application. Closing activities, teachers do not carry out activities to conclude learning materials, and (3) Problems in carrying out learning evaluations, namely teachers have difficulty conducting learning assessments because there are still students who do not collect the assignments that have been given. One of the reasons is that the assignments submitted by students are not delivered due to a poor network.